Exploring end user adoption and maintenance of a telephone-based physical activity counseling service for individuals with physical disabilities using the Theoretical Domains Framework. Issue 13 (19th June 2017) - Tomasone, Jennifer R.; Arbour-Nicitopoulos, Kelly P.; Pila, Eva; Lamontagne, Marie-Eve; Cummings, Isabelle; Latimer-Cheung, Amy E.; Routhier, François
Abstract: Purpose: In Canada, two counseling services are offered to facilitate physical activity participation among persons with physical disabilities, yet both have encountered concerns related to the recruitment and retainment of clients. The purpose of this paper is to explore factors related to service adoption among nonusers, and the barriers and facilitators to maintaining service participation among adopters. Methods: Individuals who had never enrolled in the services (nonusers, n = 13) as well as current/previous service clients (adopters, n = 26) participated in interviews based on the Theoretical Domains Framework. Transcripts were subjected to deductive thematic analysis according to participant group. Results: Fifteen themes relating to service adoption within 10 of the 12 theoretical domains were identified for nonusers, while 23 themes relating to maintenence of service participation were identified across all 12 theoretical domains for adopters. Conclusions: The findings provide strategies to improve recruitment, adoption, and retention of clients in counseling services and to enhance the experiences of targeted service users. Implications for Rehabiliation: Peer support and education for equipment use should be built into physical activity programs to encourage participation among persons with physical disabilities. Programs that encourage physical activity among individuals with disabilities should be designed by practitioners to be responsive to a variety of needs, which are addressed in the program's advertisements and offerings. The Theoretical Domains Framework is a useful framework for providing valuable insight about clients' experiences of adoption and maintenance of a behavior change service, suggesting merit in other rehabilitation settings.